2017
DOI: 10.1039/c7sc03241b
|View full text |Cite
|
Sign up to set email alerts
|

Teixobactin analogues reveal enduracididine to be non-essential for highly potent antibacterial activity and lipid II binding

Abstract: Leu10-teixobactin and Ile10-teixobactin have shown comparable activity to natural teixobactin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 21 publications
7
87
0
3
Order By: Relevance
“…Interestingly, recent discoveries of several highly active Txb analogs2224 all contain allo -End10 substitutions with medium-sized hydrophobic residues, suggesting that this secondary phosphate coordinating group at the residue 10 position is not absolutely required. Introduction of another d -Arg4 substitution of d -Gln4 in the context of Leu10 substitution of allo -End10, however, further reduces the minimal inhibitory concentrations of the Txb analog 24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, recent discoveries of several highly active Txb analogs2224 all contain allo -End10 substitutions with medium-sized hydrophobic residues, suggesting that this secondary phosphate coordinating group at the residue 10 position is not absolutely required. Introduction of another d -Arg4 substitution of d -Gln4 in the context of Leu10 substitution of allo -End10, however, further reduces the minimal inhibitory concentrations of the Txb analog 24.…”
Section: Discussionmentioning
confidence: 99%
“…This means hydrophobic interactions are expected to play significant roles in Txb's activity. Granted, most known Txb analogs with substituted mid-chain hydrophobic residues lose their antimicrobial activities,11,15,16,22 indicating that hydrophobic interactions are indeed essential for Txb–lipid II binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[144] Further comprehensive studies revealed that the synergistic inhibition of both peptidoglycan and teichoic acid synthesis results in cell-wall damage,d elocalization of autolysins,a nd ultimately cell lysis. [149][150][151] This peptide is readily available synthetically and shows excellent antibacterial activity against MRSA (MIC of 0.125 mgmL À1 )a nd 18 additional Gram-positive strains.I mportantly,t he peptide does not exhibit toxicity, neither in vitro nor in vivo (topical administration in arabbit corneal damage model), and clears infections in amouse-eye model of S. aureus keratitis as well as the approved antibiotic moxifloxacin. [146] Va rious groups have pursued the total synthesis of teixobactin and its corresponding analogues.A dditionally, NMR and crystallographic studies have given insight into the structural details of the peptide and identified the macrolactone ring to be essential for pyrophosphate binding and thus the antibiotic effect (all of this is summarized excellently by Guo et al [147] and Fiers et al [148] ).…”
Section: Reviewsmentioning
confidence: 99%
“…[144] Der Wirkmechanismus von Te ixobactin wurde mittels makromolekularer Inkorporationsstudien aufgeklärt, die eine starke Inhibition der Peptidoglycanbiosynthese nach Behandlung mit dem Wirkstoff offenbarten. [149][150][151] Dieses Peptid kann durch Standardmethoden synthetisiert werden und besitzt eine ausgezeichnete Aktivitätg egen MRSA (MIC von 0.125 mgmL À1 )u nd 18 weitere Gram-positive Stämme.E sz eigt keinerlei Toxizität in vitro und in vivo.A ußerdem heilt das Peptid durch S. aureus verursachte Keratitis-Infektionen in einem Maus-Augenmodell ähnlich gut wie das zugelassene Antibiotikum Moxifloxacin. Dazu gehçren z.…”
Section: Teixobactinunclassified